Entrepreneurial Literacy and Organizational Experience On Entrepreneurial Intention Through Entrepreneurial Attitude - Zainal Ruma; Dian Anggraece Sigit Parawansa; Anwar Anwar (Universitas Bangka Belitung, 2025)
This research explores the importance of entrepreneurship education in enhancing students’ entrepreneurial intentions and capabilities. This study emphasizes the importance of effective entrepreneurship education that combines theoretical knowledge with practical experience, highlights the relationship between self-efficacy, attitudes towards entrepreneurship, and entrepreneurial intentions and suggests that students with higher self-efficacy are more likely to value and pursue entrepreneurial opportunities. The research approach used was quantitative. We are using sample consisted of 359 respondents who were students who had taken entrepreneurship courses and had entrepreneurial intentions or owned businesses.Data analysis technique used SEM Analysis, which employs a confirmatory model.Furthermore, findings show that participation in entrepreneurship training and literacy programs significantly increases students’ confidence in their entrepreneurial abilities, thereby increasing their intention to start a new venture. The paper concludes that by equipping students with the necessary knowledge and skills, higher education institutions can effectively reduce unemployment rates and contribute to sustainable economic growth through the promotion of entrepreneurship. This study underscores the need for a paradigm shift in how students view entrepreneurship, encouraging them to become job creators rather than job seekers, ultimately leading to a more dynamic and innovative economy.